THE GOOD LIFE IN A PRECARIOUS CULTURE: STUDENT ASPIRATIONS AND THE PLANNING OF PROFESSIONAL FUTURES IN CROATIA. - ŠKOKIĆ, TEA (Croatian Journal of Ethnology & Folklore Research / Narodna Umjetnost, 2026)
This article presents a qualitative analysis of open-ended survey responses examining how university students in Croatia perceive the notion of a "good life" under conditions of precarity. It explores how young people relate to a precarious culture in which economic, temporal, and social insecurities are reflected. The focus is on responses that reveal which aspects of this culture students internalize, which they resist, and how. The paper also examines how they plan their professional futures, the obstacles they identify along the way, and the strategies they employ to overcome them.